Computational Pathology. - Louis, David N.; Feldman, Michael; Carter, Alexis B.; Dighe, Anand S.; Pfeifer, John D.; Bry, Lynn; Almeida, Jonas S.; Saltz, Joel; Braun, Jonathan; Tomaszewski, John E.; Gilbertson, John R.; Sinard, John H.; et al. (Archives of Pathology & Laboratory Medicine, 2016)
Context.--We define the scope and needs within the new discipline of computational pathology, a discipline critical to the future of both the practice of pathology and, more broadly, medical practice in general. Objective.--To define the scope and needs of computational pathology. Data Sources.--A meeting was convened in Boston, Massachusetts, in July 2014 prior to the annual Association of Pathology Chairs meeting, and it was attended by a variety of pathologists, including individuals highly invested in pathology informatics as well as chairs of pathology departments. Conclusions.--The meeting made recommendations to promote computational pathology, including clearly defining the field and articulating its value propositions; asserting that the value propositions for health care systems must include means to incorporate robust computational approaches to implement data-driven methods that aid in guiding individual and population health care; leveraging computational pathology as a center for data interpretation in modern health care systems; stating that realizing the value proposition will require working with institutional administrations, other departments, and pathology colleagues; declaring that a robust pipeline should be fostered that trains and develops future computational pathologists, for those with both pathology and non-pathology backgrounds; and deciding that computational pathology should serve as a hub for data-related research in health care systems. The dissemination of these recommendations to pathology and bioinformatics departments should help facilitate the development of computational pathology.